Plasma lipidomics in subjects with combat posttraumatic stress disorder - Konjevod, Marcela; Sáiz, Jorge; Nikolac Perkovic, Matea; Nedic Erjavec, Gordana; Tudor, Lucija; Uzun, Suzana; Kozumplik, Oliver; Barbas, Coral; Zarkovic, Neven; Pivac, Nela; Strac, Dubravka Svob (Free radical biology & medicine, 2022)
Posttraumatic stress disorder (PTSD) is complex neuropsychiatric disorder triggered by a traumatic event and characterized by the symptoms that represent large burden to patients, as well as to society. Lipidomic approach can be applied as a useful tool for discovery of novel diagnostic, prognostic and therapeutic lipid biomarkers of various disorders, whose etiology is complex and still unknown, including PTSD. Since changes in the levels of lipid metabolites might indicate impairments in various metabolic pathways and cellular processes, the aim of this lipidomic study was to determine altered levels of lipid compounds in PTSD. The study enrolled 235 male patients with combat PTSD and 241 healthy male control subjects. Targeted lipidomic analysis of plasma samples was conducted using reverse-phase liquid chromatography coupled with mass spectrometry. Lipids that have been analyzed belong to the group of ceramides, cholesterol esters, diacylglycerols, lysophosphatidylcholines, lysophosphatidylethanolamines, phosphatidylcholines, phosphatidylethanolamines, sphingomyelins and triglycerides. The levels of fifteen lipid compounds were found to be significantly different between PTSD patients and healthy control subjects, including four phosphatidylcholines, two phosphatidylethanolamines, five sphingomyelins, two cholesterol esters and two ceramides. The lipid metabolites whose levels significantly differed between patients with PTSD and control subjects are associated with various biological processes, including impairments of membrane integrity and function, mitochondrial dysfunction, inflammation and oxidative stress. As these processes might be associated with development and progression of PTSD, altered lipid compounds represent potential biomarkers that could facilitate the diagnosis of PTSD, prediction of the disease, as well as identification of novel treatment approaches in PTSD. [Display omitted] •Targeted lipidomic analysis of PTSD patients compared to healthy controls.•The concentration of 11 lipid metabolites was significantly decreased in PTSD.•The concentration of 4 lipid metabolites was significantly increased in PTSD.•The altered lipid metabolites are associated with various biological processes.•The lipid compounds might represent potential biomarkers of PTSD.